Dermatosis in Patients with Hemiplegia and Paraplegia - Osama Mohammed; Aied Mutob Turki; Saad Jwad Jasim (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objectives: To analyze the significant occurance of dermatosis among patients with hemiplegia, paraplegiacompared with other patients attending dermatology department as a control group as outpatients orinpatients.Study design an open prospective case control study.Patients and Methods: This is an open , comparative controlled investigative study conducted in Dijlahhospital of rehablitaion , enrolled 43 hemiplegic patient, 21 paraplegic patient and 65 persons as a controlpatients, between Nov. 2018 –30th June 2019. The total numbers was 129 , 91(70.5%) male patients and38 (29.5%) female patients were . The data collection tools included designed closed and open-endedquestionnaire, by using direct interviewing, and physical examination by the researcher.Results: The most common diseases that statically significant difference were as follows : Unilateral xerosiswas found in hemiplegic group 5(11.6%) cases and this was significant (P=0.04) compared to control group. Bilateral xerosis was significant among paraplegic group : 6 (28.6%) compared to 4(6.2%) among controlgroup (P=0.04 ). Unilateral exogenous eczema was found in hemiplegic patients 5(11.6%) and this wassignificant (P = 0.04) related to control group. Seborrheic dermatitis was statistically significant in paraplegicgroup 6 (28.6%) compared to 7 (10.8%) of control group. Unilateral fungal infection (Taenia paedis) washighly significant among hemiplegic group 15(34.9%) compared to 4(6.2%) control group with P value= 0.05). Bilateral fungal infection was also highly significant for paraplegic group 13(61.9%) comparedto 2(3.1%) for control group with (P value = 0.05. Unilateral bacterial infection was statically significantamong hemiplegic group 10(23.3%) compared to 5(7.7%) for control group with (Pvalue = 0.05 ) Bilateralbacterial infection was highly significant among paraplegic group 8(38.1%) compared to control 4(6.2%)with (P value = 0.05 ) . compared with control group in fungal, bactrial and xerosis , while other dermatosisas eczema , seborrheic dermatitis , psoriasis, lichen planus and viral Infection not significantly differ. Conclusion: Unilateral dermatosis significantly differs in patients with hemiplegia compared to controlgroup in fungal , bacterial and xerosis and exogenous eczema. Bilateral dermatosis significantly differsin patients with paraplegia compared to control Group in fungal, bacterial and xerosis and Seborrheicdermatitis. while other dermatosis as psoriasis , lichen planus and viral Infection not significantly differ.